Bright, near infrared emitting PLGA–PEG dye-doped CN-PPV nanoparticles for imaging applications. Issue 25 (7th March 2017) - Kemal, Evren; Abelha, Thais Fedatto; Urbano, Laura; Peters, Ruby; Owen, Dylan M.; Howes, P.; Green, Mark; Dailey, Lea Ann
Abstract : In this publication, we describe the synthesis of near-IR emitting conjugated polymer nanoparticles with an engineered surface, and their use in biological imaging. Abstract : Conjugated polymers are of interest as optical imaging probes for clinical diagnostic applications. However, clinical translation requires not only an excellent optical performance, but also an established safety profile and scalable manufacturability. Taking these factors into account, a self-assembling nanoparticle system was designed utilising the amphiphilic diblock copolymer, PLGA–PEG, to encapsulate the red-emitting conjugated polymer, CN-PPV. Encapsulation of decreasing amounts of CN-PPV (50% to 5% w/w) resulted in a decrease in nanoparticle size and an increase in optical performance (quantum yield% ∼40%). All systems were colloidally and optically stable over 60 days at 37 °C. Optimized systems were then used to encapsulate small amounts (0.5–0.8% w/w) of small molecule near-infrared dyes, NIR680 and NIR720, generating systems with shifted emission peaks >700 nm. Optimised PLGA–PEG micelles containing 5% CN-PPV and 0.5% NIR720 showed enhanced characteristics, such as a high product yield (>90%), a narrow emission peak at 720 nm, a high quantum yield of 45%, a small hydrodynamic diameter (∼104 nm), and an enhanced cytocompatibility profile compared to other systems tested in this study, i.e. no reduction in cell viability and negligible impairment of mitochondrial acitivity at higher concentrations.